2021
DOI: 10.1249/mss.0000000000002853
|View full text |Cite|
|
Sign up to set email alerts
|

Increase in Volitional Muscle Activation from Childhood to Adulthood: A Systematic Review and Meta-analysis

Abstract: Introduction Children’s maximal muscle strength is consistently lower than adults’, even when normalized to body size. Lower volitional muscle activation (VA) in children is often considered one of the main reasons for age-related differences in muscular performance. However, some recent studies have reported similar VA in children and adults, bringing into question whether there is indeed an age-related increase in VA. The purpose of this review was to determine the effect of age on VA during max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…At the neural level, multiple studies have confirmed that maturity-related increases in muscle activation, as a result of greater recruitment and utilization of motor units (particularly higher threshold/type II motor units), also lead to increases in force production without any changes to muscle cross-sectional area (13,17,19,43,46). Furthermore, maturity-related improvements in intermuscular coordination reduce agonist-antagonist coactivation, especially during dynamic contractions, and increase effective force without any changes in muscle dimensions (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…At the neural level, multiple studies have confirmed that maturity-related increases in muscle activation, as a result of greater recruitment and utilization of motor units (particularly higher threshold/type II motor units), also lead to increases in force production without any changes to muscle cross-sectional area (13,17,19,43,46). Furthermore, maturity-related improvements in intermuscular coordination reduce agonist-antagonist coactivation, especially during dynamic contractions, and increase effective force without any changes in muscle dimensions (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The key physiological mechanisms underpinning these preferential responses in youth include lower post-exercise blood lactate levels and faster clearance rates [22][23][24][25][26], an improved blood acid-base regulation [27], lower phosphocreatine depletion and faster resynthesis [28,29], and faster heart rate recovery [23,26]. Additional factors such as intramuscular synchronisation [30], agonist-antagonist coactivation [31], degree of volitional activation [32] and a reduced capability to recruit or fully employ type-II motor units may explain the lesser fatigue and muscle damage symptoms experienced by children and adolescents in contrast with adults (for detailed reviews on these topics, please see Drury et al [33] and Woods et al [32]).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, quadriceps weakness is frequently studied in anterior cruciate ligament injuries [ 5 , 6 , 7 ], because a clear distinction between neural and muscular factors contributing to this weakness is critical for optimizing rehabilitation interventions [ 8 , 9 ]. In recent years, VA of the quadriceps muscle has been commonly measured and quantified using the interpolation twitch technique (ITT), in which an electrical or magnetic pulse is applied transcutaneously to the muscle or femoral nerve during maximal voluntary knee extension [ 10 ]. Accordingly, ITT typically compares the amplitude of the double-evoked superimposed torque during the plateau of maximal voluntary isometric torque to the amplitude of the double-evoked torque at rest [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the ITT, the proportion of the control twitch that remains superimposed during a maximal voluntary isometric contraction (MVIC) is considered an indicator of the proportion of muscle that is not activated, and therefore the ratio of the superimposed evoked torque to the evoked torque at rest is commonly referred to as the activation deficit. Voluntary activation is then calculated as follows: [1 − superimposed evoked torque/evoked torque at rest × 100] [ 10 ]. However, one of the limitations of the observed percentage of VA is the large variability between repeated measurements [ 11 ], which can be explained, at least in part, by the ITT method chosen (e.g., type and number of superimposed stimuli) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%